2019
DOI: 10.18203/2349-3933.ijam20193284
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile and outcome of patients admitted with swine-origin Influenza A H1N1 virus infection at a tertiary care hospital in Western India

Abstract: Background: Most of the studies on swine flu H1N1 have been done during the pandemic phase. There was a sudden upsurge in virus activity in 2015 at many centers in India. The present study was designed to assess the current status and pattern of H1N1 infection. The primary objective of this study is to study the clinical profile of patients admitted with Swine-origin influenza A (H1N1) virus infection and Secondary objective is to study the clinical outcome in terms of morbidity and mortality.Methods: This was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Complications noted in their patients were pneumonia (45%), followed by respiratory failure and ARDS. 8 Juneja D et al in their study on dengue patients found 13.1% cases had respiratory failure. 5 Ramesh Holla et al study showed acute renal failure as the most common complication at 79.2%.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Complications noted in their patients were pneumonia (45%), followed by respiratory failure and ARDS. 8 Juneja D et al in their study on dengue patients found 13.1% cases had respiratory failure. 5 Ramesh Holla et al study showed acute renal failure as the most common complication at 79.2%.…”
Section: Discussionmentioning
confidence: 93%
“…Ambika Sharma et al study depicted that the associated comorbidities were Diabetes mellitus (19.5%), chronic kidney disease (17%) and immunosuppression (9.8%). 8 Majority of the patients -15 patients had dengue ( 30%), followed by malaria in 8 patients (16%), leptospirosis in 7 patients (14%), swine flu in 6 patients (12%), enteric fever in 4 patients (8%), cholera in 4 patients (8%), amoebiasis in 3 patients (6%), scrub typhus in 2 (4%) and lymphatic filariasis in 1 patient (2%). According to the outcome, 38 patients (76%) survived while 12 patients in our study died (24%).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation